Edukasi Literasi Digital: Peningkatan Kesadaran Masyarakat dalam Mengidentifikasi Video Hoaks Berbasis Artificial Intelligence (AI) di Kelurahan Pucangsawit, Kota Surakarta - Syifa Rana Tsary; Bambang Ali Kusumo; Ahmad Dicky Muttaqin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service activity aims to provide an understanding of the wise use of social media in digesting and accepting all information circulating on the internet from any source. The target of this activity is the PKK women's association in Pucangsawit Village, Jebres District, Surakarta City. In order to achieve the stated objectives, this activity uses normative methods by reviewing laws and regulations and empirical methods with legal counseling education methods to the community through lectures, presentation of materials/modules and showing AI-based videos. The results obtained from this Community Service agenda are increased knowledge of the participants about the importance of examining and filtering information and videos on social media that contain elements of forgery, editing using the ChatGPT or AI feature using pre-test and post-test indicators that show an increase in understanding of participants who initially still had difficulty distinguishing AI videos and are now starting to be able to identify their authenticity, so that participants are starting to be careful not to easily believe something that is not certain of its truth.